Luiza Trajano em revista : reflexões sobre a relação entre a reputação de uma CEO brasileira e a reputação corporativa - Marques, Juliana Vale (2023)
The twenty-first century is the era of mistrust and, consequently, Reputation has become one of the main risks of companies. According to global market methodologies and researches such as RepTrak® Pulse and CEO RepTrak®, the CEO Reputation impacts Corporate Reputation. This research sought to understand the role of leadership in building reputation. The main question is: how is the relationship between the Reputation of the CEO and the reputation of the company that they represent? To analyze the interface between these two constructs in the Brazilian context, we opted for the Depth Hermeneutics proposed by John Thompson (2011, 1995) and for carrying out bibliographic and documentary researches (GIL, 2014). In this research, we analyzed the representations about businesswoman Luiza Helena Trajano Inácio Rodrigues, former CEO and current chairwoman of the board of Magazine Luiza, in view of her relevance and visibility in the Brazilian corporate landscape visibility. Thus, we consolidate the results of Corporate and CEO Reputation measurement surveys published by magazines and newspapers in Brazil, from the evaluation of several audiences, and we discussed the relationship between the Reputation of the aforementioned CEO and the Reputation of Magazine Luiza based on the analysis of the cover stories of business magazines (Exame and IstoÉ Dinheiro) from 2000 to 2022, deepening the Leadership dimension. We conclude that the public trajectories of Magazine Luiza and Luiza Trajano are intrinsically linked, as well as the Corporate Reputation and Reputation of the CEO, corroborating the vast majority of reference authors